2021
DOI: 10.1111/ijfs.15380
|View full text |Cite
|
Sign up to set email alerts
|

Sensory profile of Italian Espresso brewed Arabica Specialty Coffee under three roasting profiles with chemical and safety insight on roasted beans

Abstract: Specialty coffee (SC) has been showing an increasing interest from the consumers which appreciate its traceability and the peculiar flavours from each single origin. Additionally, the processes to which coffee fruits underwent to get green coffee characterise the beans in terms of macromolecules acting as substrates during the roasting. This work evaluates via sensory analysed eight SC, roasted at light, medium, and dark level, submitted to Italian espresso extraction, to assess how different roasting levels e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
(48 reference statements)
2
4
0
Order By: Relevance
“…In detail, glucose and fructose content in dry processed beans (15 samples) is higher (P < 0.01) than honey (6 samples) and wet one (26 samples). These findings also support what provided by (Tarzia et al, 2010) in the respect of the amount of extractable saccharides in coffee obtained by different post-harvesting processes: natural process is characterised by an higher time of contact between coffee seeds and whole pulps-in comparison with honey and wet process-and by the absence of fermentation that result in the scenario mentioned above. Even if a larger number of data are required to provide with consistent results, with a preliminary analysis no differences was observed between dry (n = 4) and wet (n = 3) Robusta coffee samples.…”
Section: Aa Precursors In Green Coffeesupporting
confidence: 87%
See 2 more Smart Citations
“…In detail, glucose and fructose content in dry processed beans (15 samples) is higher (P < 0.01) than honey (6 samples) and wet one (26 samples). These findings also support what provided by (Tarzia et al, 2010) in the respect of the amount of extractable saccharides in coffee obtained by different post-harvesting processes: natural process is characterised by an higher time of contact between coffee seeds and whole pulps-in comparison with honey and wet process-and by the absence of fermentation that result in the scenario mentioned above. Even if a larger number of data are required to provide with consistent results, with a preliminary analysis no differences was observed between dry (n = 4) and wet (n = 3) Robusta coffee samples.…”
Section: Aa Precursors In Green Coffeesupporting
confidence: 87%
“…AA levels were lower than those presented by the EFSA Scientific opinion on AA in food of 2015 (the mean level, independent from the roasting degree, is 185 lg kg À1 vs 249 lg kg À1 ). Additionally, more recent scientific works (Bertuzzi et al, 2017;Schouten, Tappi, Angeloni, et al, 2020;V arady et al, 2021) provided with AA higher than ours, except for the study by (Lachenmeier et al, 2018) which reported comparable data. However, the number of samples involved in this study was less representative (only 2 samples).…”
Section: Aa Content and Correlations With Its Precursorssupporting
confidence: 61%
See 1 more Smart Citation
“…Quality control and food authentication through fast and reliable methods are essential (Coimbra et al., 2017) in a market where specialty coffees have been gaining interest from consumers who valorise the diversity of coffee origins and their influence in the perceived characteristics (Vezzulli et al., 2021). In this respect, coffee VOCs have proved their usefulness as markers of origin (Costa Freitas et al., 2001; de Toledo et al., 2017b), defects (Giacalone et al., 2019), roasting (Mateus et al., 2007; de Toledo et al., 2017a), brewing (Rocha et al., 2004) and microbial or mite contamination (Salvador et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…(Pellati et al., 2005), Ceratonia siliqua (Krokou et al., 2020) and common spices (Triaux et al., 2019). Other coffee components such as carbohydrates, dietary fibre, melanoidins, pH, acidity and phenolics content can also be object of systematisation to map nuances between coffee samples (Lopes et al., 2016; Vezzulli et al., 2021; Chindapan et al., 2022).…”
Section: Introductionmentioning
confidence: 99%